Lysosomal Storage Disease - Binod Khatiwada; A Pokharel (Journal of Nepal Medical Association, 2009)
We report a case of lysosomal storage disease diagnosed by lysosomal enzyme assay in a two year old boy with a history of gradual onset of weakness of body, poor vision, fl accid neck and spasticity in all four limbs with hyper-refl exia. On fundus examination cherry red spots were noted at macula. On performing lysosomal enzyme assay, beta-galactosidase level was considerably low. This indicates that the child is affected by lysosomal storage disease most likely GM1 gangliosidosis. The diagnosis is important because the disease is rare and it may be missed as the symptoms are similar to other neurological conditions and the diagnosis can help with future conception. Key Words: beta-galactosidase, GM1 gangliosidosis, lysosomal storage disease